Legal Certainty of Measurement and Mapping of Land Basic Maps - Ricki Azis Dzaki (Unissula, 2022)
The purpose of writing this research is to find out and analyze the implementation of the measurement and mapping of the land base map so that it can be legal certainty and beneficial for the people and the country, this research uses the normative juridical approach method. The results of the research indicate that the implementation of the measurement and mapping of the land base map is a legal certainty and provides another benefit of the certificate of right to the land is that it can provide a sense of security and peace for the owner, everything is easy to know and its nature is certain and can be held legally accountable.